Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1007/s11524-022-00693-9
|View full text |Cite
|
Sign up to set email alerts
|

An Unconditional Cash Transfer Program for Low-Income New Yorkers Affected by COVID-19

Abstract: Early in the pandemic, New York City’s public hospital system partnered with multiple philanthropic foundations to offer an unconditional cash transfer program for low-income New Yorkers affected by COVID-19. The $1000 cash transfers were designed to help people meet their most immediate health and social needs and were incorporated into healthcare delivery and contact tracing workflows as a response to the public health emergency. To better understand program recipients’ experiences, researchers conducted 150… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Similar findings were seen also in another study examining one-time cash transfers of $1000 to individuals who tested positive for COVID-19 in New York from May 2020 to May 2021. The authors concluded that after receiving a cash transfer, individuals made "rational decisions to support their health and wellbeing rather than "misusing" funds on temptation goods such as alcohol" [8]. Additionally, our study revealed that nearly all recipients surveyed were able to self-isolate for 10 days as advised, which suggests that individuals in our sample had an awareness of and desire to comply with public health measures within their community.…”
Section: Discussionmentioning
confidence: 60%
“…Similar findings were seen also in another study examining one-time cash transfers of $1000 to individuals who tested positive for COVID-19 in New York from May 2020 to May 2021. The authors concluded that after receiving a cash transfer, individuals made "rational decisions to support their health and wellbeing rather than "misusing" funds on temptation goods such as alcohol" [8]. Additionally, our study revealed that nearly all recipients surveyed were able to self-isolate for 10 days as advised, which suggests that individuals in our sample had an awareness of and desire to comply with public health measures within their community.…”
Section: Discussionmentioning
confidence: 60%
“…Seventy-nine percent of recipients reported that without the $1000 transfer, they would have had difficulty making ends meet . Most importantly, they used the money for food and rent.…”
Section: Shifting Our Mental Modelsmentioning
confidence: 99%
“…Seventy-nine percent of recipients reported that without the $1000 transfer, they would have had difficulty making ends meet. 6 Most importantly, they used the money for food and rent. Other interventions can help support multiple family members in times of duress such as when they need burial assistance or through nurse visiting programs for first-time parents.…”
Section: Shifting Our Mental Modelsmentioning
confidence: 99%
“…In New York City, where the initiative was spearheaded by the public safety-net hospital system, the cash transfers were used for food, shelter, and supplemental oxygen for home use to support COVID-19 recovery. 101 Cash transfers and other poverty reduction measures can be considered to various degrees in cities, designed based on the levels of economic inequality and prevailing political sentiment. The potential for tax policy-including expansions of the earned income and child tax credits as well as proposed taxes on wealth-to redistribute resources must be part of this conversation given the deep connection between wealth accumulation and population health and the persistence of racial wealth gaps that constrain health equity.…”
Section: Addressing Structural Determinantsmentioning
confidence: 99%
“…During the COVID‐19 pandemic, municipalities in Ontario, Canada, 100 and New York tested unconditional cash transfers. In New York City, where the initiative was spearheaded by the public safety‐net hospital system, the cash transfers were used for food, shelter, and supplemental oxygen for home use to support COVID‐19 recovery 101 …”
Section: Promising Strategies For Changementioning
confidence: 99%